Diagnostic Accuracy of Dermoscopy and Trichoscopy in Mycosis Fungoides. A Systematic Review - Michalczyk, Agnieszka; Dryżałowska-Kościan, Zuzanna; Jasińska, Magdalena; Rakowska, Adriana; Olszewska, Małgorzata; Rudnicka, Lidia; Czuwara, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2024)
Mycosis fungoides is the most common cutaneous T-cell lymphoma. The aim of this review is to assess the value of dermoscopy and trichoscopy in mycosis fungoides diagnosis. We found five dermoscopic features with the highest sensitivity: linear vessels (66.1%), white scales (60.1%), orange-yellow focal structureless areas (59.2%), dotted vessels (57.8%) and dull red background color (55.2%). We also found six dermoscopic features with the highest specificity: linear curved vessels (95.6%), linear vessels with branches (91.3%), linear vessels (88.2%), orange-yellow focal structureless areas (87.6%), purple dots/globules (82.1%) and white focal structureless areas (80.0%). The features combining high sensitivity and specificity are linear vessels and orange-yellow focal structureless areas. We also reviewed the role of dermoscopy and trichoscopy in eleven different variants of mycosis fungoides. Based on these results, we conclude that both dermoscopy and trichoscopy are valuable methods of approaching the diagnosis of mycosis fungoides, differentiating its variants, assessing skin involvement and treatment response.